2007
DOI: 10.1002/app.27680
|View full text |Cite
|
Sign up to set email alerts
|

Chemoenzymatic synthesis, characterization, and controlled release of functional polymeric prodrugs with acyclovir as pendant

Abstract: An efficient protocol for the synthesis of functional polymeric prodrugs of acyclovir with variable copolymer composition and potential liver-targeting delivery was achieved by combining enzymatic selective synthesis of polymerizable acyclovir derivatives with radical copolymerization of properly selected comonomers. Vinyl D-galactose ester (VAG), acrylic acid (AA), and methyl methacrylate (MMA) were chosen as comonomers and three novel polymeric prodrugs with acyclovir as pendant were synthesized using 2,2 0 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…dendrimers and hyperbranched polymers), and polymer brushes. [18][19][20][21][22][23][24] With antibiotic drugs, Sanchez et al prepared a library of linear poly-L-glutamic acid (PGA)-doxycycline conjugates through post-polymerization modifications of PGA carboxyl side chains into ester and amide functionalized drug linkages in efforts to investigate fibril deposits associated to familial amyloid polyneuropathy. 25 The authors demonstrated in vitro controlled release of drug from degradable ester modified PGA-drug conjugates with approximately 40% drug release within 16 days compared to the non-releasing amide alternative.…”
Section: A Introductionmentioning
confidence: 99%
“…dendrimers and hyperbranched polymers), and polymer brushes. [18][19][20][21][22][23][24] With antibiotic drugs, Sanchez et al prepared a library of linear poly-L-glutamic acid (PGA)-doxycycline conjugates through post-polymerization modifications of PGA carboxyl side chains into ester and amide functionalized drug linkages in efforts to investigate fibril deposits associated to familial amyloid polyneuropathy. 25 The authors demonstrated in vitro controlled release of drug from degradable ester modified PGA-drug conjugates with approximately 40% drug release within 16 days compared to the non-releasing amide alternative.…”
Section: A Introductionmentioning
confidence: 99%
“…The utility of MPs is well established in anticancer therapy and accomplishments of this field are highlighted by several formulations having progressed to advanced clinical trials . Surprisingly, developments of polymer therapeutics in the area of antiviral therapy are modest, and examples of polymer conjugated formulations of RBV are solitary. , Li et al reported a galactose-rich, RBV-functionalized copolymer system that self-assembled into micelles, underwent internalization by hepatic cells, and released pristine RBV over time. , However, a therapeutic benefit of these formulations was not established. Brookes et al reported the synthesis of a hemoglobin–RBV conjugate through a phosphoramidate linkage on the 5′-hydroxyl of RBV .…”
Section: Introductionmentioning
confidence: 99%
“…Undecylenic acid is an odd-numbered, monounsaturated fatty acid. Its nucleoside esters could serve as the starting materials for the synthesis of functional polymeric prodrugs with controlled release (Li et al 2008c). On the other hand, undecylenic acid has antifungal, antiviral and insect-repelling activities in which the double bond is of importance to its activities (Van der Steen and Stevens 2009).…”
Section: Introductionmentioning
confidence: 99%